(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This study aims to identify the needs of Buginese learners in mastering English in the crash course program at Neroa School, a non-formal English course institution in Soppeng Regency, South Sulawesi, Indonesia. This research method was a descriptive research. The instrument used by the researcher to collect data was a questionnaire that was previously validated by an expert. In processing data of the questionnaire, the researcher implemented an approach including stages of presentation of descriptive statistics. This approach refers to Gay (2012), Johnson & Christensen (2014), and each analysis phase adopts Nur (2015). There were five basic components represented in the questionnaire including general information, skills background of English, difficulties in learning English, learning material expectation, and learning process Expectation. The results of the study narrowed to a conclusion that respondents were generally teenagers aged 15-18 years who had difficulties in speaking and pronunciation, and lacked environmental support but had great motivation to achieve English language independence in a short time without disturbing their activities in formal education. Therefore, respondents in general were more likely to follow the crash course program which was divided into small groups of at least 1 to 3 months.